Answer:
2 3/4 C
Step-by-step explanation:
![(21+\frac{1}{4})-(18+\frac{2}{4})\\=21-18+\frac{1}{4} -\frac{2}{4} \\=3-\frac{1}{4} \\=\frac{12-1}{4} \\=\frac{11}{4} \\=2\frac{3}{4} \\or\\21\frac{1}{4} -18\frac{2}{4} \\=\frac{85}{4} -\frac{74}{4} \\=\frac{85-74}{4} \\=\frac{11}{4} \\=2\frac{3}{4}](https://tex.z-dn.net/?f=%2821%2B%5Cfrac%7B1%7D%7B4%7D%29-%2818%2B%5Cfrac%7B2%7D%7B4%7D%29%5C%5C%3D21-18%2B%5Cfrac%7B1%7D%7B4%7D%20-%5Cfrac%7B2%7D%7B4%7D%20%5C%5C%3D3-%5Cfrac%7B1%7D%7B4%7D%20%5C%5C%3D%5Cfrac%7B12-1%7D%7B4%7D%20%5C%5C%3D%5Cfrac%7B11%7D%7B4%7D%20%5C%5C%3D2%5Cfrac%7B3%7D%7B4%7D%20%5C%5Cor%5C%5C21%5Cfrac%7B1%7D%7B4%7D%20-18%5Cfrac%7B2%7D%7B4%7D%20%5C%5C%3D%5Cfrac%7B85%7D%7B4%7D%20-%5Cfrac%7B74%7D%7B4%7D%20%5C%5C%3D%5Cfrac%7B85-74%7D%7B4%7D%20%5C%5C%3D%5Cfrac%7B11%7D%7B4%7D%20%5C%5C%3D2%5Cfrac%7B3%7D%7B4%7D)
Answer:
48
Step-by-step explanation:
f(x) = x³
f'(x) = 3x²
f'(-4) = 3(-4)²
f'(-4) = 48
Answer:
The product of 10 and a number is = 10x Twice that number means 2x 36 less than twice that number= 2x-36. It is given that....The product of 10 and a number is the same as 36 less twice that same number
Step-by-step explanation:
Our equation looks like:
![5(x-6)](https://tex.z-dn.net/?f=5%28x-6%29)
This means that we will need to distribute. This means that we need to multiply everything inside the parenthesis by the number outside of the parenthesis. (<em>Note: you only distribute when variables are involved.)</em>
![(5 \cdot x)-(5 \cdot 6)](https://tex.z-dn.net/?f=%285%20%5Ccdot%20x%29-%285%20%5Ccdot%206%29)
Simplify:
![5x-30](https://tex.z-dn.net/?f=5x-30)
We cannot simplify any further, so we know that our equation, until we know what x equals, is
.
Answer:
2 • (2x - 3) • (3x - 2)
Step-by-step explanation: